Commercial octopus species from different geographical origins: Levels of polycyclic aromatic hydrocarbons and potential health risks for consumers. (November 2018) - Oliveira, Marta; Gomes, Filipa; Torrinha, Álvaro; Ramalhosa, Maria João; Delerue-Matos, Cristina; Morais, Simone
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are persistent pollutants that have been raising global concern due to their carcinogenic and mutagenic properties. A total of 18 PAHs (16 USEPA priority compounds, benzo(j)fluoranthene and dibenzo(a, l)pyrene) were assessed in the edible tissues of raw octopus ( Octopus vulgaris, Octopus maya, and Eledone cirrhosa ) from six geographical origins available to Portuguese consumers. Inter- and intra-species comparison was statistically performed. The concentrations of total PAHs (∑PAHs) ranged between 8.59 and 12.8 μg/kg w.w. Octopus vulgaris caught in northwest Atlantic Ocean presented ΣPAHs significantly higher than those captured in Pacific Ocean and Mediterranean Sea, as well as than the other characterized species from western central and northeast Atlantic Ocean. PAHs with 2–3 rings were the predominant compounds (86–92% of ∑PAHs) but diagnostic ratios indicated the existence of pyrogenic sources in addition to petrogenic sources. Known and possible/probable carcinogenic compounds represented 11–21% of ΣPAHs. World and Portuguese per capita ingestion of ∑PAHs due to cephalopods consumption varied between 1.62-2.55 × 10 −4 and 7.09-11.2 × 10 −4  μg/kg body weight per day, respectively. Potential risks estimated for low and high consumers according to USEPA methodology suggested that a regular consumption of raw octopus does not pose public health risks. Graphical abstract: Highlights: Levels of 18 PAHs were determined in three species of octopus from six geographical origins. Total concentrations in raw octopus ranged between 8.59 and 12.8 μg/kg w.w., being the compounds with 2–3 rings the predominant. Discriminant analysis allows distinction among the species of octopus vulgaris, eledone cirrhosa and octopus maya. Assessment of potential health risks indicated that a regular consumption of octopus does not pose risk for consumers.